Harvesting solutions: discover the evolution of agriculture wastewater treatment through comprehensive bibliometric analysis using Scopus database 1971-2023 - Wan Jusoh, Hajjar Hartini; Juahir, Hafizan; Mohamad Hanapi, Nur Hanis; Mohd Afandi, Nur Zulaikha; Mohd Nasir, Nurfarahana; Kurniawan, Setyo Budi; Zakaria, Nurulhuda; Muhammad Nor, Siti Mariam (Elsevier, 2024)
This bibliometric study examines scholarly research on agricultural wastewater treatment using Scopus data from 1971 to 2023 by exploring publication trends, leading countries, prolific authors, and keyword co-occurrences. This study was conducted using VOSviewer software (version 1.6.17) which enables advanced bibliometric analysis and visualization, exploring the publication networks and patterns. By using various procedures to collect and refine data, 1908 research articles were retrieved. The findings indicate a steady growth in research on wastewater treatment since the 1970 s, with a significant surge in publications in recent decades. Research on wastewater treatment for agriculture has significantly increased, particularly focusing on technologies, reuse in agriculture, and environmental impacts. However, several research gaps to be addressed, including specific focus areas within agriculture wastewater treatment, underrepresented regions in the literature, interdisciplinary approaches, long-term environmental impacts, and policy effectiveness and implementation. The analysis also highlights influential authors, institutions, and countries driving research in this field, along with the most cited publications and journals. Additionally, the study identifies research gaps and suggests future research directions in wastewater treatment. Overall, this bibliometric analysis provides valuable insights into the landscape of wastewater treatment research, its evolution over the past five decades, and its economic and policy implications. © 2024 The Authors